A Survey of Aquatic Macrophytes in the Akassa Axis of the River Nun, Niger Delta, Nigeria - AH, Gijo; KJ, Alagoa (Review of Environment and Earth Sciences, 2022)
An ecological study was conducted to measure the diversity of aquatic macrophytes and nutrient levels of the River Nun estuary around Akassa, Niger Delta, Nigeria. This was done to ascertain the current ecological status of the estuary and gauge the ecological health of the water body as a result of anthropogenic additions into the water body. Macrophye and Subsurface samples were collected from three sampling points on the estuary. Macrophyte samples were identified using standard keys while water samples were investigated for pH, Salinity, Nitrates, Phosphates, and Sulphates. Result from the study reveals the presence of 17 species of aquatic macrophytes from 8 families. All nutrient parameters were within the permissible levels. There is no significant difference (P>0.05) in pH, salinity and sulphate between stations. There is a significant difference (P<0.05) in nitrate and phosphate between stations. The diversity of macrophytes was also uniformly high in all stations. The preponderance of macrophytes in this study agrees with the aphorism that marine ecosystems contain a high diversity of living organisms. The River Nun is therefore not under any immediate ecological threat.